Latent Diabetic Macular Edema in Chinese Diabetic Retinopathy Patients - Bai, Xue; Hua, Rui (Frontiers in Medicine, 2021)
Purpose: To compare the detection rates of optical coherence tomography (OCT) and fluorescein angiography (FA) in diabetic macular edema, as well as the severity of diabetic retinopathy in both color fundus images (CFI) and FA, and to investigate the predictive factors for macular leakage in FA. Methods: This was a retrospective study, and a total of 132 eyes of 77 patients with diabetic retinopathy were enrolled. Macular OCT, FA, and CFI were reviewed and measured. Central foveal thickness was also measured. Results: The severity of diabetic retinopathy in FA was significantly higher than that in CFI (p<0.001). OCT detected 26 eyes with diabetic macular edema, which included the following: 13 eyes with cystoid macular edema; 13 eyes with serous retinal detachment; 11 eyes with diffuse retinal thickening; and 4 eyes with vitreomacular interface abnormality. In contrast, 72 out of 132 eyes (54.5%) showed macular leakage in FA, which was significantly higher than that detected by OCT (p<0.001). Compared with FA, the sensitivity and specificity of OCT in detecting DME were 30.6% and 93.3%, respectively. However, the central fovea thickness was not significantly different between patients with clinically significant macular edema (CSME, 253.1 ± 26.95 μm) and slight CSME (p=0.204). The mean central fovea thickness in diabetic macular edema (FA) eyes was 271.8 ± 66.02 μm, which was significantly higher than that (253.0 ± 25.21 μm) in non- diabetic macular edema (FA) eyes (p=0.039). The central fovea thickness in diabetic macular edema (FA) was significantly lower than that in eyes with diabetic macular edema (OCT) (p=0.014). After adjusting for age and sex, logistic regression analysis showed that the classification of diabetic retinopathy in FA was positively associated with macular leakage in FA (p<0.001). Conclusions: The severity of diabetic retinopathy is underestimated in CFI compared to that in FA. FA can detect latent diabetic macular edema, which appeared normal on OCT. The central fovea thickness is not a sensitive parameter for detecting latent diabetic macular edemas.